Traditionalism, reformism and postmodernism in Malaysia - Zakariya, Hafiz (2017)
This discourse discusses the meanings of traditionalism, reformism and postmodernism in Malaysian context.It delineates the key characteristics of each trend and how they are represented in the mainstream writing and media.